The Ability Of Green Open Space In Reducing Green House Gas (GHG) Emissions On Jalan Hertasning, Makassar City - Arfandi, Arfandi; Yusuf, Muhammad; Nasrul, Nasrul; Amda, Misdar; Hasja, Aulia Diar; Maru, Rosmini (Sainsmat : Jurnal Ilmiah Ilmu Pengetahuan Alam, 2024)
Green Open Spaces (RTH) are urban areas filled with vegetation that support ecological benefits, such as reducing greenhouse gases by absorbing CO₂ through photosynthesis. Although RTH accounts for 66 percent of the area along Jalan Hertasning, its effectiveness in absorbing CO₂ emissions from motor vehicles is not fully understood. Given the high volume of vehicles, especially during peak traffic hours, a deeper understanding of the RTH's capability to reduce CO₂ emissions is necessary. This study aims to measure CO₂ emissions from transportation, assess the RTH's ability to absorb CO₂, and develop effective RTH enhancement strategies. The research location is Jalan Hertasning in Makassar City. The method used in this study is descriptive with a quantitative approach. Results show that CO₂ emissions during peak hours cannot be fully absorbed by the existing 508 Trembles trees, which have a total absorption capacity of 1,652.07 kg/hour and cover an area of 4.4 hectares, or 75.9 percent of Jalan Hertasning. There remains 3,168.59 kg/hour of CO₂ emissions from the total 4,820.66 kg/hour during peak traffic. In addition to Trembles trees, there are other trees like Palm and Terminalia mantaly, which are still growing and not included in this study but could increase the RTH's absorption capacity in the future. The high CO₂ emissions from motor vehicles significantly impact air quality and public health. It is recommended that the government actively conduct environmental awareness campaigns focused on reducing CO₂ emissions and the importance of RTH. These campaigns can be carried out through social media, posters along Jalan Hertasning, and community outreach to reduce CO₂ levels by increasing public participation in maintaining RTH.